2011
DOI: 10.1007/s10554-011-9846-x
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation lesion morphology and intravascular ultrasound assessment

Abstract: This repot reviews the angiographic and intravascular (IVUS) assessment of coronary bifurcation lesions. Overall, bifurcation lesion anatomy and morphology is critical for technical decision making, and a key factor for successful bifurcation PCI. Optimal viewing is essential for proper angiographic assessment, especially for evaluation of the degree of SB involvement. Current classifications based on the presence or absence of significant angiographic stenosis within the three segments of the bifurcation anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…The continuous advancement of angioplasty procedures broadens the range of lesions which could be safely treated with PCI. Bifurcation stenosis in distal LMS is one such case, whose rate is systematically increasing in the population of patients subjected to PCI . Our study showed a high rate of device success with favorable acute and long‐term clinical results expressed by MACE rate at 12 months.…”
Section: Discussionmentioning
confidence: 52%
“…The continuous advancement of angioplasty procedures broadens the range of lesions which could be safely treated with PCI. Bifurcation stenosis in distal LMS is one such case, whose rate is systematically increasing in the population of patients subjected to PCI . Our study showed a high rate of device success with favorable acute and long‐term clinical results expressed by MACE rate at 12 months.…”
Section: Discussionmentioning
confidence: 52%
“…Bifurcation stenosis in distal LM stem is one of such cases and its rate is systematically increasing in the population of patients subjected to PCI [12]. This study showed a high rate of device success (100%) with favorable acute and long-term clinical results expressed by MACE rate at 12 as well as 36 months, 9.5% and 19%, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…Costa et al [5] reported about the bifurcation lesion morphology and the intravascular ultrasound assessment. It is their view that the bifurcation lesion anatomy and morphology is critical for clinical decision making, and a key factor for successful bifurcation PCI.…”
Section: X-ray Angiographymentioning
confidence: 99%
“…The assessment of coronary bifurcation lesions by IVUS was extensively reviewed by Costa et al [5]; practical aspects to be considered on a daily basis in the catheterization laboratory, such as pre-stent evaluation of vessel size, plaque morphology and its distribution, as well as post-procedure assessment of stent expansion and apposition were highlighted. Shin et al [19] applied the methodology (i.e., Shin’s method) using VH-IVUS to identify dense calcium volume and percent necrotic core to EEM as independent predictors of CK-MB elevation post successful, elective stent implantation.…”
Section: Intravascular Imagingmentioning
confidence: 99%
See 1 more Smart Citation